Analisis Majas dalam Lirik Lagu Kami Belum Tentu Karya .Feast - Hanum Ayu Lestari Setyo Ningrum; Rifqi Muhammad Zein; Najla Rafeyfa Asyla; Hanindhia Adzkiya Muthi (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2024)
Poets must be able to effectively convey unrest through their work. .Feast tends to use a variety of majas that are less popular among its listeners so that the messages that .Feast wants to convey to the listeners of its songs become varied and do not match the main message it wants to convey. This research aims to analyze the use of majas in the lyrics of the song “Kami Belum Tentu” by .Feast. This research uses a qualitative method with a literature study approach to identify and understand the types of majas used. The results of the analysis show that there are 12 types of majas with a total of 51 uses of majas, including metaphor, personification, hyperbole, irony, paradox, and others. This research reveals that the variety of majas in songs provides aesthetic appeal while strengthening critical messages. However, the complexity of meaning in the lyrics is often a challenge for listeners, especially those who are less familiar with the majas used. Through this research, it is hoped that listeners can understand the meaning of songs more comprehensively, so that the message of the singer can be conveyed effectively.